2017
DOI: 10.1007/s00264-017-3481-7
|View full text |Cite
|
Sign up to set email alerts
|

Weight-bearing recommendations after operative fracture treatment—fact or fiction? Gait results with and feasibility of a dynamic, continuous pedobarography insole

Abstract: Our study results show that, despite physical therapy training, weight-bearing compliance to recommended limits was low. Adherence to the partial weight-bearing task was further decreased over time. Uncontrolled weight-bearing recommendations should thus be viewed with caution and carefully considered as fiction. The presented insole is feasible to determine weight bearing continuously, could immediately help define real-time patient behaviour and establish realistic, individual weight-bearing recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 29 publications
0
46
0
2
Order By: Relevance
“…The study was limited by the fact that there was no blinding of patients, treating physicians or outcome assessors; however, it is unclear whether blinding is truly necessary in this pragmatic trial. A potential criticism also mentioned by Dehghan et al is the potential noncompliance of patients to their designated postoperative care regimen [4,9]. Patient noncompliance could lead to a higher rate of complications as described previously, although this was absent in the present study [20].…”
Section: Discussionmentioning
confidence: 47%
“…The study was limited by the fact that there was no blinding of patients, treating physicians or outcome assessors; however, it is unclear whether blinding is truly necessary in this pragmatic trial. A potential criticism also mentioned by Dehghan et al is the potential noncompliance of patients to their designated postoperative care regimen [4,9]. Patient noncompliance could lead to a higher rate of complications as described previously, although this was absent in the present study [20].…”
Section: Discussionmentioning
confidence: 47%
“…For example, Braun et al used for their study a continuously measuring pedobarography insole to measure weightbearing in trauma patients with fractures of the lower extremities. The study showed that, despite physical therapy training, weight-bearing compliance to recommended limits was low (36). Overall, despite their willingness to comply, patients often do not adhere to the suggested restrictions on weight-bearing and increase their weight-bearing as fracture healing progresses.…”
Section: Resultsmentioning
confidence: 98%
“…While instructions for rehabilitation given to patients may be clear, patient compliance with a non-weightbearing or limited weight-bearing regime has been found to be poor (34,35). A number of studies found that patients had actually exceeded the prescribed amount of partial weight-bearing even though their self-reported compliance was high (35,36). For example, Braun et al used for their study a continuously measuring pedobarography insole to measure weightbearing in trauma patients with fractures of the lower extremities.…”
Section: Resultsmentioning
confidence: 99%
“…The insole includes pressure and force sensor that measure the force applied at key bearing points under the foot. Such a selflearning adaptive weightbearing monitoring system also can deliver electrical, mechanical, and/or audio feedback to encourage a patient to load the optimal target weight, the patient is given continuous feedback for improving rehabilitation (25,26). Another recommendation for future research is the use of Virtual Stress Testing, which provide a non-invasive estimate of a healing bone through a CT scan and has the potential to provide a quantitative, objective measure to identify fractures who could safely handle bearing weight (27).…”
Section: Discussionmentioning
confidence: 99%